"Managing Up": Cultivating Relationships With Practice Leaders. Issue 2 (18th February 2022) - Wahab, Rifat A; Brown, Ann; Vijapura, Charmi; Mahoney, Mary C
Abstract: "Managing up" for the radiologist means developing and cultivating work relationships to benefit high-level stakeholders and the institution at large, and to maximize one's own effectiveness. Today's breast radiologists are responsible for more than image interpretation and image-guided interventions. Radiologists' roles and responsibilities have evolved to include clinical initiatives, staff development, quality improvement, and administrative tasks where management skills are needed. To be successful in these roles, developing skills to manage up will allow radiologists to be more effective team members. In this article, we discuss tactics to start developing strategies for managing up, including how to understand practice leaders and create meaningful relationships; explain various work style personalities and how to navigate them; describe how to understand oneself, including strengths and weaknesses; and, finally, provide tips on how to begin to cultivate managing up skills.